Relocation branding: a strategic framework for attracting talent from abroad. Issue 1 (3rd June 2014) - Silvanto, Sari; Ryan, Jason
Abstract : Purpose: – The global migration and movement of talent plays an important role in the economic growth and competitiveness of many nations. In coming decades, it is anticipated that there will be increased competition between countries to attract the best and brightest. The World Economic Forum (2011) has recommended using nation branding strategies to attract talent. In response to this recommendation, the purpose of this paper is to propose a strategic framework and terminology for branding nations to attract highly skilled workers. Based on a review of the literature, it recommends five strategic vision drivers that can help countries brand themselves in an appealing and compelling way to talented professionals. This paper also recommends the term "relocation branding" to describe the practice of branding nations, regions and cities to attract talent. Design/methodology/approach: – This paper examines the literature on nation branding and talent mobility to propose a conceptual framework of five vision drivers for branding destinations to attract talent. It also discusses how these vision drivers can be used in the context of an overall branding initiative and campaign. Findings: – This paper finds that the determinants of talent mobility are complex and overlapping. Highly skilled temporary and permanent migrants have a broad range of concerns and interests when they voluntarily choose a country to live and work in. This paper argues that, given these complexities, a more tailored and multidimensional understanding of talent mobility is necessary to effectively craft a branding strategy that will appeal to the highly skilled. A clear vision, demonstrating an understanding of the challenges of moving between countries, has to be integrated into the brand from the outset. Originality/value: – This paper is one of the only in-depth studies of nation branding for the purpose of attracting temporary and permanent skilled migrants. The value of this paper is significant as it provides a framework for strategically creating and positioning nation brands to attract highly skilled workers.